Peningkatan Kualitas Bibit Tanaman Multy Purpose Tree Species (MPTs) Sebagai Upaya Mendukung Kegiatan Rehabilitasi - Zulkaidhah Zulkaidhah; Rukmi Rukmi; Ariyanti Ariyanti; Dewi Wahyuni; Abdul Hapid; Rahmawati Rahmawati (Journal on Education, 2023)
Forestry plant nurseries are one of the efforts to support land rehabilitation activities that have been launched by the Government. Nursery activities not only contribute to environmental sustainability but are expected to provide many benefits both economically, environmentally, and socially. The seeds produced are expected to be used to rehabilitate and plant critical land, vacant land, and unproductive land. MPTS types of plants are currently widely used as plants for rehabilitation activities because they have financial advantages, namely high economic value, and are liked by the community. The service method used is counseling, training, and mentoring. Counseling and training include good MPTS plant nursery techniques so they can produce quality seeds, nurseries using quality/certified and selected seeds, using good planting media that can support nutrient availability for seedling growth and how to do top grafting on seedlings MPTS plants to obtain good and quality seeds. The results of the implementation of the Service Results Dissemination Program activities went well and smoothly with 100% realization of the activity. The counseling and training activities carried out included counseling on quality MPTs plant nursery techniques and for training activities carried out procedures for making solid organic fertilizer (compost) and top grafting techniques on MPTs plant seeds. Realization of activities can be seen from the successful shoot grafting seedlings.